Reconhecendo os invisíveis: análises socioeconômicas e de garantia de direitos da população em situação de rua de Mossoró/RN - Martins, Priscilla Karla Roseno (Universidade Federal Rural do Semi-Árido, 2019)
In this paper, it was discussed about the homeless population of Mossoró/ RN, focusing on the work done at the social approach level through the Centro de Referência da Assistência Social (CREAS) and the socioeconomic studies of the Consultório na Rua to analyze how the National Policy for the Homeless Population has been implemented in the Municipality of Mossoró/RN especially considering the intervention strategies adopted to guarantee rights and the socioeconomic situation of the people served. The methodology used in the investigative process consisted of documentary and bibliographic research, as well as the use of field research. In the bibliographic research we resorted to authors such as: Gotijo (2014); Miranda (2016); Holanda (2019), as well as documentary research, prioritizing Decree Nº 7,053 of December 23, 2009 establishing the National Policy for Homeless People, and it is concluded that the work currently carried out with homeless people in the municipality of Mossoró/RN and who is a public with many complex demands, which can be overcome by interests of the subjects and throughout interventions, from the construction of projects of different lives, together multiprofessional teams and users of services, and guarantees of basic rights, allowing individuals to observe their quality of life beyond the realities currently posed as concrete.
Monografia
Keywords: População em Situação de Rua; Direitos Sociais; Saúde e Assistência Social; Homeless Population; Social Rights; Health and Social Assistance; CIENCIAS SOCIAIS APLICADAS::DIREITO